Polycyclic aromatic hydrocarbons and polychlorinated biphenyls in the harbour of Naples (Southern Italy): time and spatial distribution patterns - Feo, Maria Luisa; Sprovieri, Mario; Gherardi, Simona; Sammartino, Simone; Marsella, Ennio (Springer Nature, 2010)
Seventeen parent polycyclic aromatic hydrocarbons (PAHs) and 38 congeners of polychlorinated biphenyls were measured at five different sediment depths (between the surface and ~300 cm below the seafloor) at 160 sites in Naples harbour. Total PAH (ΣPAH) and PCB (ΣPCB) concentrations ranged between 0.012–21.73 − nd 0.001–0.222 mg kg − 1, respectively. For PAHs, an evident and progressive decrease in concentration with depth documents the effects of a more intense anthropic impact of this group of pollutants in the recent period. A selected number of PAH isomer pairs (phenanthrene/anthracene, fluoranthene/pyrene and benzo(a)anthracene/crysene) were used to distinguish between contaminants of pyrolitic and petrogenic origin. More than 90% of PAHs present at the different depths of the studied sediments indicate pyrolitic industrial origins. On the other hand, relatively high concentrations of three- and four-ring PAHs suggest a limited contribution of vehicular emissions to the contamination of sediments. An unexpected and systematic increase of ΣPCB concentration, exceeding values approved by international regulations, was found in the studied sediments, testifying to the uncontrolled discharge to the studied area from industrial and commercial activity on nearby land. Ecotoxicological risk levels calculated for PAHs suggests a relatively elevated level of toxicity in surface sediments decreasing with depth and very low toxicity values associated to PCB toxicity.
Keywords: Contaminantes orgánicos del agua; PAH; PCB; Contaminantes orgánicos; Puerto de Nápoles